2022
DOI: 10.1002/agj2.21010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of warming and drought stress on winter wheat in Jiangsu Province, China

Abstract: We used the World Food Studies (WOFOST) model to analyze meteorological, soil, and winter wheat (Triticum aestivum L.) growth period data in Xuzhou, Huaian, and Changzhou, Jiangsu Province from 2008 to 2017. The data collected were used to study the effects of warming and drought on winter wheat yield and dry matter accumulation. The simulation results showed that single warming stress (1, 2, and 3 ℃), drought stress (mild, moderate, and severe), and combined drought and warming stress can reduce the yield of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Similarly, the maximum reduction in DM was obtained under severe combined stress (25% FC at 35°C) mainly for Hmira and Karim. These results are in complete accordance with several other studies for the variety Karim [ 98 100 ]. Indeed, a reduction in the hydration of durum wheat induces a reduction in biomass [ 101 – 103 ].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, the maximum reduction in DM was obtained under severe combined stress (25% FC at 35°C) mainly for Hmira and Karim. These results are in complete accordance with several other studies for the variety Karim [ 98 100 ]. Indeed, a reduction in the hydration of durum wheat induces a reduction in biomass [ 101 – 103 ].…”
Section: Discussionsupporting
confidence: 93%
“…Sha et al. (2022) analyzed the effects of warming and drought on winter wheat yield and dry matter accumulation. They concluded that highest yield wheat reduction rate was 25.5% under the condition of single warming, and the yield reduction rate increased by 5% when the soil relative humidity decreased by 10% under short‐term drought.…”
Section: Resultsmentioning
confidence: 99%
“…Agricultural technologies must adapt quickly to F I G U R E 3 Main components of new technologies overcome potential environmental issue, such as warming and drought stress. Sha et al (2022) analyzed the effects of warming and drought on winter wheat yield and dry matter accumulation. They concluded that highest yield wheat reduction rate was 25.5% under the condition of single warming, and the yield reduction rate increased by 5% when the soil relative humidity decreased by 10% under short-term drought.…”
Section: Environmental Factors Affecting Crop Production and Qualitymentioning
confidence: 99%
“…Three DSSAT-Wheat models have been used to quantify the impact of water management practices on crop water stress and wheat yield (Jing et al, 2021). The WOFOST model has been used to study the effects of warming and drought on winter wheat yield and dry matter accumulation in Jiangsu Province from 2008 to 2017 (Sha et al, 2022). Wu et al (2019) used the Agricultural Production System Simulator (APSIM) model to investigate the response mechanism of wheat yield to long-term drought stress in southwest China.…”
Section: Introductionmentioning
confidence: 99%